Strategi Pengembangan Potensi Puncak Wakila Sebagai Objek Wisata Alam - Hendra Tamrin; La Ode Amaluddin; Surdin; La Harudu (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2024)
The development of tourism potential often arises problems such as the lack of precise strategies used in its development. Therefore researchers aim to know: 1) internal factors in efforts to develop potential; 2) external factors in efforts to develop potential; and 3) an efficient strategy for the potential development of Puncak Wakila as a natural tourist attraction in Kondongia Village, Lohia District, Muna Regency. This type of research uses qualitative research using descriptive methods. Data analysis techniques used to find internal and external factors based on development theory, and IFAS-EFAS analysis. SWOT matrix are used to formulate a suitable strategy for the development of Puncak Wakila potential. The results of this study that suitable strategies used in the development of the potential of Puncak Wakila are: 1) policy strategy, namely policy making related to the development of tourism potential; 2) facility strategies related to the provision of adequate facilities; and 3) promotion strategies are related to tourism marketing.